Modern derivatives pricing and credit exposure analysis : theory and practice of CSA and XVA pricing, exposure simulation and backtesting /: theory and practice of CSA and XVA pricing, exposure simulation and backtesting. (2015) - Lichters, Roland, 1967-; Stamm, Roland, 1970-; Gallagher, Donal, 1969-
No abstract available